Burden of Food-Borne Trematodiases in China: Trends from 1990 to 2021 and Projections to 2035 - Yanzheng Zou; Yihu Lin; Yili Qian; Luqiu Tao; Gao Tan; Hongru Zhu; Li Pan; Xiaoli Liu; Yu He; Wei Wang (Tropical Medicine and Infectious Disease, 2024)
To assess the burden of food-borne trematodiases in China from 1990 to 2021 and project the burden through 2035, data were captured from the Global Burden of Disease Study (GBD) 2021 datasets. The estimated prevalent food-borne trematodiase cases were 33.32 million (95% uncertainty interval (UI): 29.25–38.35 million) in China in 2021, contributing to 768,297.4 disability-adjusted life years (DALYs) (95% UI: 383,882.8–1,367,826.1). The number of prevalent cases and DALYs declined by 9.02% and 18.11%, and a downward decline was seen in age-standardized prevalence and DALY rates (estimated annual percentage change: −0.96% and −1.21%, respectively). A higher prevalence and DALY rates were observed among males than females, and the middle-aged group bore the highest burden, while the older population showed the most rapid increase in prevalent cases and DALY numbers. Projected DALY counts and rates remain stable through 2035 using the Bayesian age–period–cohort (BAPC) model. These findings demonstrate a decline in the burden of food-borne trematodiases in China from 1990 to 2021; however, the prevalence remained high, which contributed considerably to disability and premature death. Continued control efforts and targeted interventions are essential to further reducing the burden of food-borne trematodiases in China.